2013
DOI: 10.4236/ajac.2013.41008
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of S-Enantiomer in Montelukast

Abstract: A simple and rapid Supercritical Fluid Chromatography (SFC) Method has been developed to isolate and characterize the S-Isomer of Montelukast by using normal phase Amylose based AS-H with 250 mm × 30 mm, 5 microns column using a mobile phase system containing super critical fluid carbon dioxide (CO 2 ) and the percentage of 2-Propanol as a mobile phase (85:15) and detection at 230 nm. The isolated S-Isomer was characterized by using FT-IR, ESI-MS, HPLC and 1H NMR. The purity of isolated S-Isomer is about 98%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The International Conference of Harmonization (ICH) Q7 guiding principal mandates strict control of the S-enantiomer content in montelukast sodium bulk drug 15 . Moreover, literature has shown that montelukast sodium, as an LTD4 receptor antagonist, is superior to its S-enantiomer in both in-vitro and in-vivo studies 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The International Conference of Harmonization (ICH) Q7 guiding principal mandates strict control of the S-enantiomer content in montelukast sodium bulk drug 15 . Moreover, literature has shown that montelukast sodium, as an LTD4 receptor antagonist, is superior to its S-enantiomer in both in-vitro and in-vivo studies 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Analyst® TF 1.6 soware was used for data acquisition and data processing. The ion spray voltage for the DuoSpray™ ion source in ESI mode 19,20 was maintained at 4500 V and the temperature was set at 450 C. The auxiliary gas and curtain gas used were high purity nitrogen. Zero air was used as the nebulizer gas.…”
Section: Lc/ms/msmentioning
confidence: 99%
“…5). 35 The enantioseparation of chlorinated drugs [36][37][38] is of interest because, along with fluorine, the chlorine atom is also incorporated in several biologically active compounds. Indeed, it is considered to be isosteric and isolipophilic with the methyl group, able to alter the metabolism and is effective in inhibiting metabolic oxidation.…”
Section: Drugsmentioning
confidence: 99%